The effect of Si and S on the stability of bcc iron with respect to tetragonal strain at the Earth's inner core conditions. Issue 12 (18th June 2013) - Cui, Hang; Zhang, Zhigang; Zhang, Yigang
Abstract [1] The Earth's inner core is primarily composed of iron, but the stable crystalline structure of iron under core conditions still remains uncertain. The body‐centered cubic (bcc) phase has been suggested as a possible candidate to explain the observed seismic complexity, but its stability at core conditions is highly disputed. In this study, we utilized thermodynamic integration techniques based on extensive first‐principles molecular dynamics simulations to analyze the combining effects of high temperature and impurities on the stability of bcc structure with respect to tetragonal strain. According to our simulations, a small amount of Si/S permitted by seismological data at high temperature increases the stability of the bcc structure at high pressure, but not enough to achieve complete stability. This means the bcc‐structured iron is highly unlikely to present in the Earth's inner core.